Distribution and Retrieval of Modules: Investigating the Experiences of Elementary Teachers - Marjory Manoza Rosales; Cynic J Tenedero; Rejulios M Villenes (Research Synergy Foundation, 2024)
This is a quantitative descriptive study that determines the implementation level and challenges of the distribution and retrieval of modules at Don Gregorio C. Yumul Sr. Elementary School in terms of safety measures, organizing the learning modules, and the process of implementing modular distance learning in the academic year 2022. A survey questionnaire was used to determine the different experiences in the distribution and retrieval of modules. This study was conducted in Don Gregorio C. Yumul Sr. Elementary School with one principal and fourteen teachers, for a total of fifteen teachers from October to March of school year 2021-2022 respectively. In terms of safety measures and organizing the learning modules it has a positive result feedback from the respondents as they were responsible when it comes to their health and the people around them. The implementation level in terms of the process of implementing modular distance learning shows that every teacher ensures that the learners understand the module given to them and that they make sure to tack and monitor every learner's accomplishment despite the learning mode, thus, the hypothesis is rejected and interpreted as significant. It is recommended that the teacher should always remind or give clear instructions to the parents on the activities that the learners should do, and by retrieving the modules on time, the teacher must have active communication with the parents/guardians and also create other strategies or plans for how they can monitor the process of implementing the modular learning.